Disciplinary Literacy in English Language Arts: Exploring the Social and Problem-Based Nature of Literary Reading and Reasoning - Rainey, Emily C. (Reading research quarterly, 2017)
Despite many calls for K-12 disciplinary literacy instruction—instruction that teaches students the specialized ways of reading, writing, and reasoning of the academic disciplines—there are questions about what disciplinary literacy instruction means for the prominent school domain of English language arts. This article investigates the disciplinary literacy practices and teaching approaches of 10 university-based literary scholars who participated in semistructured interviews and verbal protocols with literary fiction. Findings point to the fundamentally social and problem-based nature of academic work with literature and to a set of six shared literary literacy practices that scholars use in their work with literature. These findings were generated as part of a larger study that compared literacy practices and teaching approaches of 10 university-based scholars and 12 high school English language arts teachers (Rainey, 2015).